Pelaksanaan Pertanggungjawaban Sosial Perusahaan (Corporate Social Responsibility) PT. Sari Husada Cabang Yogyakarta Terhadap Lingkungan Sosial - Jejen Hendar (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Indonesia is the welfare state that promotes the livelihoods of both material and immaterial society as stated in the Undang-undang Dasar of 1945, Section 28H paragraph (1). Various corporate activities bring real impact on both the quality of human life on individual, community, and throughout life. Deforestation, global warming, environmental pollution, poverty, ignorance, disease, life and access to clean water, ongoing until finally came the concept of corporate social responsibility or CSR. UU No. 40 of 2007 on Limited Liability Companies, which every company should pay attention to the surrounding environment or social responsibility through Corporate Social Responsibility (CSR). PT. Sari Husada as a publicly listed company and is engaged in dairy nutrition based in the city center. Problems that occur if PT. Sari Husada perform CSR should set out in the Company Law. the question is how the company's concern about the environment and how companies impact on the environment